Nonlinear dynamics of the coupled exciton-cavity system - Meier, Torsten; Koch, M.; Shah, J. (Quantum Electronics and Laser Science Conference)
In recent years the linear emission dynamics of microcavities containing an optical absorber has been a subject of intense research. For strong coupling between the cavity and the absorber, the spectrum of the coupled system shows two peaks and the linear dynamics of the coupled system is dominated by pronounced oscillations at the normal mode frequency.1 Yet, the uniqueness of the coupled absorber-cavity system cannot be concluded from its linear dynamics.

Multiple Exciton Coherence Sizes in Photosynthetic Antenna Complexes viewed by Pump-Probe Spectroscopy - Meier, Torsten; Chernyak, V.; Mukamel, S. (The Journal of Physical Chemistry B)
The pump−probe signal from the light-harvesting antenna LH2 of purple bacteria is analyzed using a Green function expression derived by solving the nonlinear exciton-oscillator equations of motion (NEE). A microscopic definition of the exciton mean free path (Lf) and localization size (Lρ) is given in terms of the off-diagonal elements of the exciton Green function and density matrix, respectively. Using phonon-induced (homogeneous) and disorder-induced (inhomogeneous) line widths compatible with superradiane measurements, we find that at 4.2 K the localization size is Lρ = 15 and that the shift ΔΩ between the positive and negative peaks in the differential absorption is determined by a different effective size Lf/2 = 5.6 associated with the exciton mean free path. Our model further predicts the recently observed superradiance coherence size determined by Lρ.

Wohnzimmer und Satelliten. Die Empirie der Fernsehwissenschaften - Adelmann, Ralf; Stauff, Markus (montage/av. Zeitschrift für Theorie und Geschichte audiovisueller Kommunikation)

Bericht aus der Arbeitsgruppe Erziehungswissenschaft - Herzig, Bardo (Neue Medien – neue Aufgaben für die Lehrerausbildung)

Praxis- und theorieorientierte Entwicklung und Evaluation von Konzepten für pädagogisches Handeln - Tulodziecki, G.; Herzig, Bardo

Der Kinderfilm im Multimedia-Zeitalter - Herzig, Bardo (Perfo 1/1997)

Ibarra, Andoni/Mormann, Thomas, “Structural Analogies between Mathematical and Empirical Theories”, in: J. Echeverria et al. (eds.), The Space of Mathematics, Walter de Gruyter: Berlin 1992 [Zbl 0839.00019], 31–46 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 874.00011)

Technik, die Gesellschaft schafft. Soziale Netzwerke als Ort der Technikgenese - Riedl, Lars; Weyer, Johannes; Kirchner, Ulrich; Schmidt, Johannes F. K.
Dieses Buch verknüpft Technikgeneseforschung und Netzwerkanalyse, um auf diese Weise ein soziologisches Modell von Innovationsprozessen zu entwickeln, das auf unterschiedlichste Fallbeispiele anwendbar ist. In kritischer Auseinandersetzung mit bisherigen Konzeptualisierungen von Technikentwicklung wird Technikgenese hier als ein mehrstufiger Prozeß der sozialen Konstruktion von Technik aufgefaßt, der von wechselnden Akteurkonstellationen getragen wird und mehrere Phasen durchläuft. Für den Erfolg einer neuen Technik ist es entscheidend - so lautet eine der Schlüsselthesen -, ob es den Technikkonstrukteuren gelingt soziale Netzwerke zu konstituieren und derart zu stabilisieren, daß sie eine solide Basis für ein Technikprojekt bilden. Dieses Modell wird an empirischen Beispielen sowohl staatlich getragener Technikentwicklung (Airbus, Transrapid) als auch privatwirtschaftlich erzeugter Technik (Personal Computer, Astra-Satellit) überprüft. Da sich diese Fälle trotz ihrer Heterogenität nach einem einheitlichen Prinzip beschreiben lassen, ist es möglich, Ansatzpunkte für eine soziale Gestaltung von Innovationsprozessen zu identifizieren.
Keywords: Technikgenese; Akteur-Netzwerke; Phasenmodell; Transrapid; Airbus; Innovationsprozesse; Technologiepolitik

Mit Hacke, Helm und Zeichenbrett hinab ins dunkle Mittelalter. Archäologische Stadtkerngrabung am Kötterhagen im Zentrum von Paderborn - Ströhmer, Michael (Mitteilungen des Vereins für Geschichte an der Universität Paderborn)

Singular Unitary Highest Weight Representations via Geometric Quantization - Hilgert, Joachim (Reports on Math. Physics)